ANTICANCER ACTIVITY OF CRUDE EXTRACTS OF TWO SPONGES, FASCIOSPONGIA CAVERNOSA DOC VAR. BROWN & FASCIOSPONGIA CAVERNOSA DOC VAR. YELLOW - SUJATHA PEELA, (International Journal of Pharma and Bio Sciences, 2016)
This study reports the in vitro screening of two marine sponges (Porifera) collected from the coastline of Bay of Bengal, Visakhapatnam Coast, in the search for novel pharmaceuticals. In this study, the anticancer activity exhibited by crude sponge extracts from Fasciospongia cavernosa doc var. brown and Fasciospongia cavernosa doc var. yellow from Visakhapatnam coast of Bay of Bengal were reported. Antitumor activities were determined by a cell growth assay with three different tumor cells lines, HeLa (Human cervical cancer), A-549 (Human lung cancer cell line) and HEK-293 (Human kidney cell line) using SRB method. Among the two varieties of sponges Fasciospongia cavernosa doc var. brown displayed a high anticancer activity. Fasciospongia cavernosa doc var. brown marine sponge exhibited strong cytotoxic activities against all tumor cell lines. These extracts are currently undergoing further analysis to identify the active constituents.